DE VOLTA À PRAIA GRANDE: o velho centro com o novo discurso - Silva, Georgia Patrícia da (2010)
Analysis of the neighborhood of Praia Grande, São Luís, Maranhão, from the program of preservation and revitalization and marketing strategies for selling the city on the global market has been consolidating in a "postcard" which is a reference golden age of colonial and imperial period and the "certified" World Cultural Heritage granted by UNESCO. It describes the urban landscapes in the area, production and space race with the conduct of the changes in the functional transformation of the neighborhood when he was elevated to the point of attraction for tourism due to the collection of cultural heritage. It studies the process of the use, misuse and reuse of urban space and built items, permeated by conflicts of interests and classes. It shows that the district of Praia Grande is facing infrastructure problems, especially with the lack of public investment, which has been widely denounced by tourists and traders. It concludes that, during the process of revitalizing the neighborhood of Praia Grande, cultural goods were re-appropriated by the government in the discourse on the built heritage, a fact which helped to promote the city show at the same time that overshadowed the urban and emptying rationality on the capital's historic center, masking the problems of the old urban center.